On the monograph by A. Savarin “Craniological Atlas of Belarusian Mammals. Insectivores” - Mykola Tovpinets (Theriologia Ukrainica, 2019)
The atlas presents photographs of various sides of the skull of species belonging to the order Lipotyphla of the fauna of Belarus. The most important craniological features of the species are indicated. Examples of the significance and relationship between external and craniological characters are given. The important aspect of creating photographic databases for prompt exchange of information and visual comparison of samples from different geographic locations in order to study variation is presented. Pathological-anatomical monitoring allows obtaining important information for ecological studies. It is emphasized that morphological analysis of the inner surface of cranial structures will have gain more importance since their changes might indicate different pathologies related to ecological features of the environment. It is also essential that craniological material from raptor pellets can be also involved into such studies.